Inclusive growth, full employment, and structural change implications and policies for developing Asia - Felipe, Jesus ca. 20./21. Jh (Anthem Press, 2020)
'Inclusive Growth, Full Employment, and Structural Change: Implications and Policies for Developing Asia' discusses policies to achieve inclusive growth in developing Asia, including those relating to agriculture, investment, certain state interventions, monetary, fiscal, and the role of the state as employer of last resort. Felipe argues that in order to deliver inclusive growth, Asian leaders must commit to the goal of full employment
Title from publisher's bibliographic system (viewed on 21 Sep 2020)
Keywords: Full employment policies / Asia; Labor market / Asia; Manpower policy / Asia; Wirtschaftswachstum; Vollbeschäftigung; Strukturwandel; Wirtschaftspolitik; Asien